Dietary Supplementation With Acer truncatum Oil Promotes Remyelination in a Mouse Model of Multiple Sclerosis - Xue, Yuhuan; Zhu, Xiaoyan; Yan, Wenyong; Zhang, Zhihan; Cui, Enhui; Wu, Yongji; Li, Cixia; Pan, Jiarong; Yan, Qijiang; Chai, Xuejun; Zhao, Shanting (Frontiers in Neuroscience, 2022)
Background: Multiple sclerosis is characterized by demyelination mediated by immune in the central nervous system. Fatty acids are vital for sphingomyelin synthesis in the daily diet, while insufficient intake of essential fatty acids may be responsible for the increased demyelination and reduced efficiency of remyelination processes. The oil of Acer truncatum oil contains high concentration of unsaturated fatty acids, especially nervonic acids, the essential component of the myelin sheath. Objective: Here, we investigated the underlying influences of Acer truncatum oil on the stimulation of remyelination in a cuprizone mouse model of demyelination. Methods: Cuprizone (0.2% in chow) was used to establish a mouse model of demyelination. Acer truncatum oil was administrated to mice during remyelination. Following techniques were used: behavioral test, histochemistry, fluorescent immunohistochemistry, transmission electron microscope. Results: Mice exposed to cuprizone for 6 weeks showed schizophrenia-like behavioral changes, the increased exploration of the center in the open field test, increased entries into the open arms of the elevated plus-maze, as well as demyelination in the corpus callosum. After cuprizone withdrawal, the diet therapy was initiated with supplementation of Acer truncatum oil for two weeks. As expected, myelin repair was greatly enhanced in the demyelinated regions with increased mature oligodendrocytes (CC1) and myelin basic protein (MBP). More importantly, the supplementation with Acer truncatum oil in the diet reduced the schizophrenia-like behavior in the open field test and the elevated plus-maze compared to the cuprizone recovery group. The results revealed that the diet supplementation with Acer truncatum oil improved behavioral abnormalities, oligodendrocyte maturation and remyelination in the cuprizone model during recovery. Conclusions: Diet supplementation with Acer truncatum oil attenuates demyelination induced by cuprizone, indicating that Acer truncatum oil is a novel therapeutic diet in demyelinating diseases.